PERKAWINAN PASANGAN BEDA AGAMA PASCA SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 - Afifa Khairunnisa; Sonny Dewi Judiasih; Betty Rubiati (Jurnal Humaniora & Sosial Sains, 2024)
Indonesia, with its many religions, certainly provides opportunities for interfaith marriages, coupled with the absence of laws and regulations that explicitly prohibit interfaith marriages. The issuance of SEMA Number 2 of 2023 prohibits judges from granting applications for registration of interfaith marriages, thus closing the opportunity for the registration of interfaith marriages that have been determined in advance by the court. This study aims to ensure the validity of marriages of couples of different religions after the issuance of SEMA Number 2 of 2023 and the acquisition of legal protection for children born from marriages of couples of different religions whose ratification is rejected by the court based on the relevant laws and regulations. The validity of interfaith marriages is reviewed from Article 2 paragraph (2) of the Marriage Law that its implementation is based on each person's religion. The implementation of marriage registration has been prohibited by SEMA Number 2 of 2023. The absence of marriage registration has several negative impacts on the children born, namely the child's position becomes illegitimate, difficulty in meeting the administrative requirements for birth registration, and uncertainty in choosing their own religion for the child because it affects the lineage of their parents.